Influence of weather condition on incidences of ergot of Bazra in Gujrat- A preliminary study - KAZI, S. K.; VENKATARAMAN, S. (MAUSAM, 1982)
The meteorological conditions pre disposing for an outbreak of the ergot disease of bajra are examined. Heavy precipitation with afternoon relative humidity about 80 percent followed by clearing of weather favours the initiations and full expression of the disease.